Temperature sensitivity of SOM decomposition is linked with a K‐selected microbial community. (25th March 2021) - Li, Hui; Yang, Shan; Semenov, Mikhail V.; Yao, Fei; Ye, Ji; Bu, Rencang; Ma, Ruiao; Lin, Junjie; Kurganova, Irina; Wang, Xugao; Deng, Ye; Kravchenko, Irina; et al.
Abstract: Temperature sensitivity (Q10 ) of soil organic matter (SOM) decomposition is a crucial parameter to predict the fate of soil carbon (C) under global warming. Nonetheless, the response pattern of Q10 to continuous warming and the underlying mechanisms are still under debate, especially considering the complex interactions between Q10, SOM quality, and soil microorganisms. We examined the Q10 of SOM decomposition across a mean annual temperature (MAT) gradient from −1.9 to 5.1°C in temperate mixed forest ecosystems in parallel with SOM quality and bioavailability, microbial taxonomic composition, and functional genes responsible for organic carbon decomposition. Within this temperature gradient of 7.0°C, the Q10 values increased with MAT, but decreased with SOM bioavailability. The Q10 values increased with the prevalence of K‐strategy of soil microbial community, which was characterized by: (i) high ratios of oligotrophic to copiotrophic taxa, (ii) ectomycorrhizal to saprotrophic fungi, (iii) functional genes responsible for degradation of recalcitrant to that of labile C, and (iv) low average 16S rRNA operon copy number. Because the recalcitrant organic matter was mainly utilized by the K‐strategists, these findings independently support the carbon quality‐temperature theory from the perspective of microbial taxonomic composition and functions. A year‐long incubation experiment was performed to determine the response of labile and recalcitrant C pools to warming based on the two‐pool model. The decomposition of recalcitrant SOM was more sensitive to increased temperature in southern warm regions, which might attribute to the dominance of K‐selected microbial communities. It implies that climate warming would mobilize the larger recalcitrant pools in warm regions, exacerbating the positive feedback between increased MAT and CO2 efflux. This is the first attempt to link temperature sensitivity of SOM decomposition with microbial eco‐strategies by incorporating the genetic information and disentangling the complex relationship between Q10 and soil microorganisms. Abstract : Temperature sensitivity (Q10 ) of soil organic matter (SOM) decomposition tends to increase in response to climate warming, in parallel with the declined SOM bioavailability (increasing bio‐recalcitrance), and the increasing dominance of microbial K‐strategy, as indicated by the high ratios of oligotrophic to copiotrophic taxa, ectomycorrhizal to saprotrophic fungi, functional genes responsible for degradation of recalcitrant to that of labile C, and low average 16S rRNA operon copy number. Since K‐strategy is relevant to the decomposition of recalcitrant compounds, these findings independently confirm the carbon quality‐temperature (CQT) theory, disentangling the complex Q10 ‐SOM quality–microbes relationship.